Common Fixed Point Theorems on Compatibility and Continuity in Soft Metric Spaces - Bhardwaj, Ramakant; Singh, Shweta; Gupta, Sonendra; Sharma, Vipin Kumar (Communications in Mathematics and Applications, 2021)
In this paper, basic notions of soft sets are introduced and some important properties of soft metric spaces are established. It is shown that soft metric extensions of several important fixed point theorems for metric spaces can be directly deduce from comparable existing results. Some examples are given to validate and illustrate the approach. Obtained results modify, improve, sharpen, enrich and generalize various known results.